Pelatihan Dasar Microsoft Office Word dan Power Point Bagi Siswa Penyandang Disabilitas SLB Nurul Ikhsan Ngadiluwih - Natalinda Pamungkas; Iqlima Zahari; Erika Devi Udayanti; Wildan Mahmud; Karmila Karmila; Chornelius Aneba Moza Ikratama; Dian Restu Adji (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This Community Partnership Program (PkM) activity was carried out at SLB Nurul Ikhsan Ngadiluwih Kediri. The service location is approximately 12 km from the PSDKU campus of Dian Nuswantoro University, Kediri. In the current era, almost all students are required to be able to master technology, especially information technology. Students' mastery of technology is used to support learning activities and improve skills. One of the software technologies used to support educational activities is Microsoft Office Basic, namely Microsoft Word and Microsoft Power Point. Special Education or Special Schools (SLB) are schools intended for children with special needs to receive basic services that can help them gain access to education. SLB is an educational institution that provides education to children with special needs so that it can be used as a provision for the child's future growth and development. Nurul Ikhsan SLB was founded by a private foundation, namely the Nurul Ikhsan Education Foundation, located in Ngadiluwih Village, Ngadiluwih District, Kediri Regency, East Java. One of the visions, missions and goals of SLB Nurul Ikhsan is that students are equipped according to their type of ability, with the aim that SLB graduates have high basic social characteristics, have knowledge, skills and independence as the basis needed to continue their studies to the next level of education. higher level, working in society, socializing and being able to develop themselves in accordance with the principles of lifelong education. Through this training activity, it is intended to provide insight and additional skills to Nurul Ikhsan SLB students to explore and practice directly operating Microsoft Word and Microsoft Power Point.